Voluntary blood donation in a rural block of Vellore, South India: A knowledge, attitude and practice study - Akhil Kurup; Avanish Jha; Shalini Sahu; K. N. C. Sindhu; Arun Bhatt; Anu Mary Oommen (Wolters Kluwer Medknow Publications, 2016)
Context: There is a shortage of voluntary blood donors in developing countries which are, therefore, more dependent on replacement donors. Aim: To study the knowledge, attitude, and practices regarding voluntary blood donation in a rural block in Vellore, South India. Settings and Designs: A cross-sectional survey in randomly selected villages of a rural block in Vellore, South India. Materials and Methods: Knowledge, attitude, and practices were assessed using a pilot-tested, semi-structured, interviewer-administered questionnaire on randomly chosen rural adults aged between 18 and 60 years. Results: Of the 104 individuals interviewed, 90% were aware of voluntary blood donation, the main source of this awareness being television. Nearly, two-thirds of the participants felt they would fall sick by donating blood and that women and manual laborers were not capable of blood donation. Among the interviewed, 70.3% were of the opinion that blood can purchased with money. Only 44% were willing to donate blood on a voluntary basis. Perceived weakness and a misconception on the apparent lack of blood were the major reasons for unwillingness to donate blood. There was a significant association between willingness to donate blood and educational status as well as occupation, with the less educated and manual laborers unwilling to donate blood on a voluntary basis (odds ratio [OR] = 3.758, confidence interval [CI] = 1.54-9.156; OR = 5.333, CI = 1.429-19.90, respectively). Conclusions: The study found that although awareness on voluntary blood donation among individuals in the rural community was widespread, hesitancy to donate blood in real life situation was high. Since voluntary unpaid donors are the best candidates for blood donation, community being the best available source, education, and motivation of the community should play a greater role in increasing voluntary blood donation.